Epigallocatechin gallate, in comparison with other pretreatments, improves resin-enamel bonding following bleaching. Issue 13 (3rd July 2021) - Zhang, Denghui; Zhang, Jiawei; Zhu, Tianer; Guan, Xiaoxu; Zhou, Yi
Abstract: With the popularity of dental bleaching, the need of immediate restoration following bleaching is increasing urgently. This study aimed to seek methods to improve the bonding strength to enamel of composite resin after bleaching. The best concentration and reaction time of Epigallocatechin gallate (EGCG) regarding bonding strength after bleaching were determined using micro tensile bond strength test (µTBS) to enamel. Bovine Incisors were randomly divided into six groups. Composite resin was built-up after different pretreatments (deionized water, 10% sodium ascorbate, the remineralization fluid, EGCG of the optimal concentration and 75% ethanol) for 1 h after bleaching. µTBS and scanning electron microscopy (SEM) were used to evaluate the effect to immediate bonding strength after bleaching. The mode of failure was determined by a stereo-microscope at 50-fold magnifications. Treatment with 10% EGCG for 30 mins was selected as the best concentration and reaction time. Bleaching led to significantly reduced shear bond strength ( p  < 0.05). 10% EGCG produced higher µTBS than other groups ( p  < 0.05). The resin tags after treatments with the four pretreatments were significantly longer and thicker than the control groups under SEM. The application of 10% EGCG could rescue the resin-enamel bond strength after bleaching.